A first attempt to evaluate the toxicity to Phaeodactylum tricornutum Bohlin exposed to rare earth elements - Siciliano, Antonietta; Sabatino, Manuela; Paone, Antonietta; Padilla Suarez, Edith Guadalupe; Toscanesi, Maria; Brouziotis, Antonios Apostolos; Gambino, Edvige; Saviano, Lorenzo; Trifuoggi, Marco; Guida, Marco; Libralato, Giovanni (Frontiers in Environmental Science, 2022)
The increasing use and demand of rare earth elements in many emerging technologies is leading to a potentially higher input to the marine environment. This study compared for the first time the effect of lanthanum (La), cerium (Ce), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), dysprosium (Dy), and erbium (Er) to the microalga Phaeodactylum tricornutum Bohlin. The algal growth inhibition was investigated after 72 h of exposure. The median effect concentrations (EC50) ranged from 0.98 mg/L to 13.21 mg/L and elements were ranked as follows: Gd > Ce > Er > La > Eu > Nd > Dy > Sm. The comparison of predicted no effect concentrations (PNEC) for hazard and risk assessment with measured environmental concentrations showed that ecological risks deriving from REEs could be present, but limited to specific environments like estuarine waters. The results support evidence of actions to manage the REE impact in seawater environments, looking to improve the monitoring tailored to the different and dynamic nature of ecosystems.